2015
DOI: 10.1007/s00421-015-3128-6
|View full text |Cite
|
Sign up to set email alerts
|

The physiological responses to repeated upper-body sprint exercise in highly trained athletes

Abstract: sprint decrement of 11.7 ± 4.1 %. Cycle rate remained unchanged, whereas work per cycle progressively decreased (P < 0.05). m. triceps brachii and m. latissimus dorsi were highly desaturated already after the first sprint (all P < 0.05), whereas the response was delayed for m. biceps brachii and m. vastus lateralis. Correspondingly, increases in VO 2 mainly occurred over the first two sprints (P < 0.05) and plateaued at approximately 75 % of VO 2peak . 1RM correlated with power during the first four sprints an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Moreover, the increased day to day reliance on the lower body musculature for ambulation compared to the upper body may induce favourable training adaption's which allow for a reduced decrement in RSA. In support of these findings the present study found the % decrement in total work performed across the five sprints to be approximately 11.4% for the upper body which is in agreement with a recent study conducted using elite cross country skiers [26], however differs compared to previous studies which have reported between approximately 5.4% and 8.5% for the lower body in endurance and team athletes respectively [15]. These findings, in conjunction with reports of a significant correlation between blood buffer capacity and RSA [27] further suggests a reduced buffering capacity of the upper body musculature, which consequently leads to a higher decrement in work performed and thus decreased RSA performance.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the increased day to day reliance on the lower body musculature for ambulation compared to the upper body may induce favourable training adaption's which allow for a reduced decrement in RSA. In support of these findings the present study found the % decrement in total work performed across the five sprints to be approximately 11.4% for the upper body which is in agreement with a recent study conducted using elite cross country skiers [26], however differs compared to previous studies which have reported between approximately 5.4% and 8.5% for the lower body in endurance and team athletes respectively [15]. These findings, in conjunction with reports of a significant correlation between blood buffer capacity and RSA [27] further suggests a reduced buffering capacity of the upper body musculature, which consequently leads to a higher decrement in work performed and thus decreased RSA performance.…”
Section: Discussionsupporting
confidence: 93%
“…Not restricting upper-body movement (as is more commonly seen when UBP is used during training and competition), would have led to a different use of the trunk in UBP compared to ACE, in particular in the comparison of PARA versus AB. In UBP, trunk movement can easily contribute to increased power production and thereby elevated MR (Hegge et al 2015). In comparison, due to the asynchronous arm movements in ACE, there is a lower contribution of the trunk movement to power production.…”
Section: Discussionmentioning
confidence: 99%
“…An ErgStick (Endurance Sports Research Limited, United Kingdom) was connected to the PM4 monitor of the Concept2 ski ergometer and the application Float (ErgStick Ltd, United Kingdom) continuously recorded power output (PO) and stroke rate. The ergometer’s software has previously been validated with force and velocity measurements (Hegge et al 2015). The ACE was custom-made from a road-bike (White, XXL Sport & Villmark AS, Norway) and equipped with an electronical brake system for indoor cycling (CompuTrainer™, RacerMate®, Inc., Seattle, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When maximal sprint efforts are repeated, however, there is a rapid deoxygenation at exercise onset that slowly recovers at sprint cessation . The evolution of peaks and nadirs across the NIRS signal is often used to describe the quality of metabolic recovery between sprint bouts . Because of the rapid oxygenation adjustments and short duty cycle of repeated‐sprint exercise, accurate identification of peaks and nadirs in the NIRS signal is critical.…”
Section: Introductionmentioning
confidence: 99%